Mahogany Shoot Borer, Hypsipyla grandella (Zeller) (Insecta: Lepidoptera: Pyralidae: Phycitinae) - F. W. Howard; Michael A. Merida (EDIS)
The mahogany shoot borer, Hypsipyla grandella (Zeller), bores in twigs and seed capsules of trees in the mahogany family (Meliaceae), especially mahogany species (Swietenia spp.) and cedro, known also as Spanish-cedar and tropical-cedar (Cedrela spp.). It is an important economic pest and has been the subject of concerted research efforts in several tropical countries. It is the only species of Hypsipyla in Florida, where it is a pest of West Indies mahogany (Swietenia mahagoni Jacquin), a native tree that is frequently planted as an ornamental or shade tree in southern Florida. This document is EENY-336, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: December 2004. Revised: January 2005.